Development of an Approach of High Sensitive Chemiluminescent Assay for Cystatin C Using a Nanoparticle Carrier - Sun, Yuanjie; Tao, Liang; Ma, Ying; Yang, Shuya; Zhang, Xiyang; Jin, Boquan; Zhang, Zhujun; Yang, Kun (Frontiers in Chemistry, 2020)
Cystatin C is a significant cysteine protease inhibitor in the human body and is proposed as a novel marker of glomerular filtration rate for kidney injury detection. In this article, we report an ultra-sensitive, simple, and rapid chemiluminescence immunoassay method for cystatin C detection using functionalized mesoporous silica nanoparticles. After a three steps hydrolysis, the amino-functionalized MSN encapsulating dye resulted in a hydrophobic environment for fixing the dye and amino groups for biological modification. The NaIO4 immobilization method maintained the activity of the antibody notably well. The sandwich immunoassay using two monoclonal antibodies was chosen for its selectivity. The analysis demonstrated that the detection limit was 0.0029 ng⋅mL⁻¹ and linear response within the range of 0.0035 to 0.5 ng⋅mL⁻¹ (R2 = 0.9936). The relative standard deviation (RSD) for 11 parallel measurements of 0.25 ng⋅mL⁻¹ CysC was 4.7%. The automated chemiluminescence analyzer could detect 96 wells continuously. The results demonstrated that this method is ultra-sensitive, simple, and rapid for detecting cystatin C.